Occlusal Features and Temporomandibular Joint Disorder: A Cross-Sectional Study - Mustafa M. Al-Khatieeb; Layth M. Nissan; Yasir R. Al-Labban; Mushriq Abid (International Journal of Dentistry)
Background. Understanding the correlation between temporomandibular joint disorder (TMD) parameters and various occlusal features can play a significant role in diagnosing and treating occlusal problems and their potential consequences on TMD. Objectives. To investigate the relationship of occlusal features and some of the TMD parameters. Study Design and Sampling. The current cross-sectional study was conducted on 200 TMD patients seeking dental treatment at different dental centers in Baghdad city, aged 18–35 years. All participants underwent assessment for occlusal features, which were molar and canine classifications, overjet, posterior buccal or lingual crossbites, and overbites, and TMD parameters (muscle pain, TMJ pain, and clicking) using the Chi-square test for statistical analysis. Results. Regarding molar classification, there were strong positive correlations between subjects with TMD and having different molar classifications (class I, II, and III) bilaterally or unilaterally; furthermore, there were strong positive correlations between subjects with TMD and having different canine classifications. Moreover, there were significant correlations between subjects with increased, normal, or decreased overjet and the TMD parameters. In addition, there were weak positive correlations between TMD occurrence and buccal or lingual posterior crossbite. On the other hand, there were significant correlations between subjects with a decreased overbite and the presence of TMD parameters. Conclusion. TMD had a multifactorial background rather than dependability on a specific molar or canine classification type. There was also a correlation between overjet and TMD muscle pain, while decreased overbite was correlated to muscle and TMJ pain. Conversely, there is no vital correlation between posterior buccal or lingual crossbite occurrence and TMD parameters.